Tinjauan Lama Waktu Pendistribusian Rekam Medis Rawat Jalan di Rumah Sakit Umum Bhakti Asih - Adinda Pratiwi; Lily Widjaja; Muniroh Muniroh; Daniel Happy Putra (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Medical record is written or recorded information regarding identity, history taking, physical determination, laboratory, diagnosis of all medical services and actions provided to patients and treatment, whether inpatient, outpatient or receiving emergency services. Distribution in the health sector, especially medical records, has the meaning of a process of distributing medical records to each polyclinic addressed by the patient according to the medical record number. Minimum Service Standards (SPM) are provisions regarding the type and quality of basic services in the speed of providing medical records, the standard time for providing medical records for outpatient services is 10 minutes. This research was conducted at Bhakti Asih Hospital located at Jalan Raden Saleh No. 10, Karang Tengah, Tangerang City, Banten 15157. The purpose of this study was to determine the length of time for the distribution of outpatient medical records at Bhakti Asih General Hospital. This type of research uses descriptive quantitative methods. Data collection techniques used are observation and interviews. In this study, the population was all outpatient medical records in the period June 2021 with a sample of 96 outpatient medical records, using the Incidental/Convenience sampling technique. The results of this study can be seen that 52 medical records (54.16%) have met the SOP 10 minutes, while 44 medical records (45.83%) have not met the SOP 10 minutes. The time of calculating the distribution of outpatient medical records with 96 samples for 10 days with a total time of 984 minutes obtained an average time of distribution of outpatient medical records of 10.25 minutes.